“Frigate Pallada” by I. A. Goncharov in Context of Travelogue Genre: Narrative Strategies of Official Traveller - N. V. Konstantinova (Научный диалог, 2018)
The article is devoted to the analysis of the phenomenon of “travel prose” by I. A. Goncharov in the context of the tradition of Russian travelogue of the 19th century. Traditionally, in the process of analysis of text material (travel notes) the principles and forms of combining the two main narrative strategies are distinguished: the author-documentarian, ethnographer, historian and author-writer, artist. The subject of this study was the individual narrative strategies of the official traveller. “Frigate Pallada” by I. A. Goncharov is defined as a “landmark” in the evolution of travelogue genre. Different narrative strategies of the author-traveller, perceiving the world from the point of view of two minds - “modest official” and “new Argonauts” - are revealed and compared. The phenomenon of narrative in travel essays by I. A. Goncharov is characterized, on the one hand, as a syncretic text, combining elements of scientific and literary travel, on the other hand, as an individual author’s text, demonstrating the destruction of various patterns and stereotypes of the genre form of travelogue, developed by the 1850-ies. The author comes to the conclusion that in the travel prose by I. A. Goncharov there is an increase in the subjective and personal principle, which in the narrative is expressed by the constant change of narrative strategies and demonstrates the constant search for a point of view on the world.